Knowledge, Attitude, and Practice Regarding Cancer Screening Tests Among Health Workers in a University Hospital in Turkey - Soylar, Pinar; Ozer, Ali; Yuksekol, Ozlem Dogan; Ulucan, Mihriban (Springer, 2020)
Health workers play an important role in the early detection of cancer and encouraging people to participate in screening tests. This study aimed to analyze the knowledge, attitude, and practice of health workers regarding cancer screening and to determine variables that affect their behavior in undergoing in screening tests. This descriptive study was conducted among 475 health workers (84 assistant doctors, 306 nurses, 65 midwives, and 20 other professionals) in a university hospital. The questionnaire included sociodemographic questions (age, profession, years of experience, and family history of cancer) and questions about the workers' knowledge, attitude, and practice regarding cancer screening. It was found that half of the participants had inadequate knowledge of cancer screening methods (50.3% for Pap smear, 57.5% for mammography, 68.4% for colonoscopy, and 54.3% for fecal occult blood). Although the attitudes of the health workers were mostly positive (above 90% for all screening tests), their practice of screening methods was low (for example 25.7% of them practiced mammography and 4.2% pap smear). Older health workers, those with a family history of cancer, and those with more than 11 years of experience tended to participate in cancer screening tests more often than health workers who were younger, had no family history of cancer history, and whose experience was less than 10 years (p < 0.05). A health worker's profession was not an important factor in their practice of undergoing screening tests (p > 0.05).
Keywords: Early detection of cancer; Knowledge; Attitude; Practice; Health; Screening